The Impact of the STCA System on ATCs’ Conflict Projection Ability in Jakarta APP/TMA - Dicky Nugraha; Ichyu Machmiyana; Rany Adiliawijaya P (CV. AFDIFAL MAJU BERKAH, 2026)
This study aims to analyze the influence of the Short Term Conflict Alert (STCA) system on the conflict projection ability of Air Traffic Controllers (ATC) at the APP/TMA Jakarta Unit. The increasing air traffic volume by 19.6% between 2022 and 2025 has heightened operational complexity, emphasizing the need for effective decision-support systems. A quantitative research method was employed using a survey approach involving 105 active ATCs with at least two years of experience. The variables examined include Perception of STCA (X), Situational Awareness (SA), Workload Management (WM), Training and Experience (TE), and Conflict Projection Ability (Y). Data analysis consisted of validity, reliability, normality, Pearson correlation, and multiple linear regression tests. The results indicate that STCA has a positive and significant influence on conflict projection ability, with an Adjusted R² value of 0.80 and a multiple correlation coefficient (R) of 0.90. Among the predictors, SA and TE make the strongest contributions, while WM functions as a supporting factor. In conclusion, the integration of STCA technology and human performance factors plays a crucial role in enhancing safety and efficiency in air traffic control operations at APP/TMA Jakarta.